Proton MR spectroscopy of the foramen of Monro region in patients with tuberous sclerosis complex Espectroscopia de prótons por RM da região do forame de Monro em pacientes com complexo esclerose tuberosa - Arnolfo de Carvalho-Neto; Isac Bruck; Sérgio A. Antoniuk; Edson Marchiori; Emerson L. Gasparetto (Arquivos de Neuro-Psiquiatria)
PURPOSE: To evaluate with 1H-magnetic resonance spectroscopy (MRS) the metabolites rations of the foramen of Monro's region in patients with tuberous sclerosis complex (TSC). METHOD: Twelve patients with TSC and an age and gender-matched control group underwent MR imaging at a 1.5T scanner, and 1H-MRS at the foramen of Monro level with a multivoxel acquisition. Similar volumes of interest were selected in each side of the foramen of Monro and in the basal ganglia (lentiform nuclei). The obtained N-acetylaspartate (NAA), creatine (Cr) and choline (Cho) peak amplitude values and ratios were studied. The statistical analysis was performed and p<0.05 was considered statically significant. RESULTS: There was no significant difference between the NAA/Cr and Cho/Cr ratios near to the foramen of Monro and basal ganglia of the TSC patients compared with the controls (p>0.05). CONCLUSION: The NAA/Cr and Cho/Cr ratios near to the foramen of Monro and basal ganglia of TSC patients are similar to the rations obtained in the control group. OBJETIVO: Avaliar através de espectroscopia de prótons as relações dos metabólitos da região do forame de Monro em pacientes com complexo esclerose tuberosa (CET). MÉTODO: Doze pacientes com CET e um grupo controle pareado por sexo e idade realizaram RM em aparelho de 1,5T, e a espectroscopia de prótons foi obtida ao nível do forame de Monro com aquisição multi-voxel. Volumes de interesse similares foram posicionados em cada lado do forame de Monro e nos gânglios da base (núcleos lentiformes). Os valores das relações e amplitudes de pico do N-acetilaspartato (NAA), creatina (Cr) e colina (Cho) foram estudados. A análise estatística foi realizada e valores de p<0,05 foram considerados estatisticamente significativos. RESULTADOS: Não houve diferença significativa entre as relações NAA/Cr e Cho/Cr na região do forame de Monro e nos gânglios da base dos pacientes com CeT comparados com os controles (p>0,05). CONCLUSÃO: As relações NAA/Cr e Cho/Cr na região do forame de Monro e nos gânglios da base de pacientes com CET são semelhantes àquelas obtidas no grupo controle.